Visual task performance in the blind with the BrainPort V100 Vision Aid. (2nd October 2016) - Stronks, H. Christiaan; Mitchell, Ellen B.; Nau, Amy C.; Barnes, Nick
ABSTRACT: Introduction : The BrainPort® V100 Vision Aid is a non-invasive assistive device for the blind based on sensory substitution. The device translates camera images into electrotactile stimuli delivered to the tongue. The BrainPort has recently received the CE mark and FDA approval and it is currently marketed to augment, rather than replace, the traditional assistive technologies such as the white cane or guide dog. Areas covered : In this work, we will review the functional studies performed to date with the BrainPort and we will highlight the critical factors that determine device performance, including the technology behind the BrainPort, the impediments to assessing device performance, and the impact of device training and rehabilitation. Expert commentary : The BrainPort enables blind people to perceive light, identify simple objects, recognize short words, localize simple objects, and detect motion and orientation of objects. To achieve this, proper rehabilitation and training regimes are crucial.